Brokerage Commission Schedules - BRENNAN, MICHAEL J.; CHORDIA, TARUN (Journal of Finance, 1993)
ABSTRACT It is generally optimal for risk‐sharing reasons to base a charge for information on the signal realization. When this is not possible, a charge based on the amount of trading, a brokerage commission, may be a good alternative. The optimal brokerage commission schedule is derived for a risk‐neutral information seller faced with risk‐averse purchasers who may differ in their risk aversion. Revenues from the brokerage commission are compared with those from a fixed charge for information and the optimal mutual fund management fee.